2021
DOI: 10.3390/nu13113767
|View full text |Cite
|
Sign up to set email alerts
|

Association between Parents’ Perceptions of Preschool Children’s Weight, Feeding Practices and Children’s Dietary Patterns: A Cross-Sectional Study in China

Abstract: Parental perception of children’s weight may influence parents’ feeding practices, and in turn, child dietary intake and weight status; however, there is limited evidence generated for preschoolers. The aim of this cross-sectional study was to investigate associations between Chinese parents’ perceptions of child weight, feeding practices and preschoolers’ dietary patterns. Participants (1616 parent-child pairs) were recruited from six kindergartens in Hunan, China. Parents’ misperception, concern, and dissati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Characteristics of the included studies are shown in Table 1 . The studies were published between 2001 and 2022, conducted in the US ( n = 12) [ 21 , 24 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], Australia ( n = 6) [ 26 , 27 , 75 , 76 , 77 , 78 ], Brazil ( n = 4) [ 28 , 30 , 50 , 79 ], Sweden ( n = 4) [ 22 , 80 , 81 , 82 ], China ( n = 2) [ 83 , 84 ], the Netherlands ( n = 1) [ 85 ], Ethiopia ( n = 1) [ 29 ], the UK ( n = 1) [ 86 ], Mexico ( n = 1) [ 87 ], South Korea ( n = 1) [ 88 ], Portugal ( n = 1) [ 23 ], India ( n = 1) [ 25 ], and France ( n = 1) [ 74 ]. The study designs were a cross-sectional study ( n = 32) and a cohort study ( n = 3) [ 23 , 26 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Characteristics of the included studies are shown in Table 1 . The studies were published between 2001 and 2022, conducted in the US ( n = 12) [ 21 , 24 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], Australia ( n = 6) [ 26 , 27 , 75 , 76 , 77 , 78 ], Brazil ( n = 4) [ 28 , 30 , 50 , 79 ], Sweden ( n = 4) [ 22 , 80 , 81 , 82 ], China ( n = 2) [ 83 , 84 ], the Netherlands ( n = 1) [ 85 ], Ethiopia ( n = 1) [ 29 ], the UK ( n = 1) [ 86 ], Mexico ( n = 1) [ 87 ], South Korea ( n = 1) [ 88 ], Portugal ( n = 1) [ 23 ], India ( n = 1) [ 25 ], and France ( n = 1) [ 74 ]. The study designs were a cross-sectional study ( n = 32) and a cohort study ( n = 3) [ 23 , 26 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…The caregivers were typically mothers ( n = 19). Only four studies used a random sampling method [ 27 , 29 , 67 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations